Capital budgeting techniques in sri lanka a survey - Pratheepkanth, P.; Premkanth, P. (University of Jaffna, 2018)
Making a strong investment decision is vital as resources are scarce and the investment is expected to add to the value of the firm. Capital budgeting (CB), a key input to achieving that goal, is the rational allocation of limited capital across a plethora of viable prospective investment. This study investigates whether CB techniques differ significantly among the firms in Sri Lanka as an example of emerging country. The questionnaires posted to 150 Sri Lankan-listed firms asked about firm and respondent demographics along with various aspects of CB techniques. Sri Lankan firms tend to consider PBP as the most important CB technique and IRR as the next in importance. Scenario approach is the most widely used techniques for assessing capital-investments risk. Sri Lankan firms rely to some extent on the WACC when estimating the cost of capital. Sri Lankan firms have little interest in RO analysis. The NPV method is less prevalent in Sri Lanka. In complex real-world situations, reconciling the outputs of a multifaceted approach to CB methods is more likely to give the depth and width of input needed to achieve an optimal capital investment plan.
Keywords: Capital budgeting; Investment analysis; Resources; Cost of capital